2005
DOI: 10.1272/jnms.72.60
|View full text |Cite
|
Sign up to set email alerts
|

Pemphigoid Nodularis: Two Case Studies and Analysis of Autoantibodies before and after the Development of Generalized Blistering

Abstract: We report 45- and 61-year-old women with generalized prurigo nodularis-like eruption whose clinical, histologic and immunopathologic features were consistent with the diagnosis of pemphigoid nodularis. In one case, nodular lesions preceded the onset of generalized blistering by two years and in the other, no definite blister nor erosion was seen except for some appearing on the soles during the course of the disease. Western immunoblotting of EDTA-separated epidermal extracts revealed that the 230-kD bullous p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
1
6
0
1
Order By: Relevance
“… 16 investigated retrospectively the humoral response to BP180 by a commercially available BP180‐NC16A ELISA in 25 elderly patients with pruritus, and found that 12% of the subjects showed IgG reactivity against the NH 2 terminus of the BP180 ectodomain (Table 4). Finally, a series of case reports detected the same autoantibody profile in patients with pruritic prepemphigoid compared with full‐blown BP with tense blisters which in some cases developed later on 23–28 . Notably, the present study also detected IgG against BP180 and BP230 in two elderly individuals with immediate‐type allergy who had experienced neither pruritic nor bullous skin lesions.…”
Section: Discussionsupporting
confidence: 74%
“… 16 investigated retrospectively the humoral response to BP180 by a commercially available BP180‐NC16A ELISA in 25 elderly patients with pruritus, and found that 12% of the subjects showed IgG reactivity against the NH 2 terminus of the BP180 ectodomain (Table 4). Finally, a series of case reports detected the same autoantibody profile in patients with pruritic prepemphigoid compared with full‐blown BP with tense blisters which in some cases developed later on 23–28 . Notably, the present study also detected IgG against BP180 and BP230 in two elderly individuals with immediate‐type allergy who had experienced neither pruritic nor bullous skin lesions.…”
Section: Discussionsupporting
confidence: 74%
“…However, sometimes blisters cannot be observed throughout the whole course of the disease, making diagnosis substantially difficult. Many authors have defined this particular form of BP pemphigoid nodularis (PN) [25][26][27][28][29][30][31][32][33][34] Fig. 1.…”
Section: Atypical Presentations Of Bullous Pemphigoidmentioning
confidence: 99%
“…2,[10][11][12][13][14] In a Swiss study population, 20% of 160 patients diagnosed with BP did not have blisters. 15 In the literature, patients have been reported with itch combined with immunopathologic findings compatible with BP but without the formation of blisters, when followed up for several months or even years. [5][6][7][8][9]11,14,[16][17][18][19] In previous studies, most of these patients were older than 70 years, with a follow-up of 4 months to 6 years.…”
Section: Discussionmentioning
confidence: 99%